Du double affrontement ontologique/axiologique autour de la résilience aux risques de catastrophe : les spécificités de l’approche française - Béatrice Quenault (VertigO, 2013)
The growing interest given to resilience within urbanized societies may be interpreted as the sign of an assumed incapacity to reduce a number of climatic risks. However, behind the implicit search of the “acceptable disaster” linked with the enhancement of the resilience concept, there is a double occasion of confrontation: firstly, an ontological confrontation (with an epistemological feature) between two opposite visions of resilience; secondly, an axiological confrontation (with a political nature) between to contrasted approaches of risk management in order to prevent disasters. Taking note of that context, this article, through the specificities of the French approach of public policies for managing risks of climatic disaster in urban milieu, aims at underlying the existing confrontation between the dominant vision focused on short term reactive resilience, on one side, and the less widely held vision focused on long term proactive resilience, on the other side. Whereas the first approach corresponds to a mere use of resilience as an instrument to pursue the risk management and urban planning in continuity with the “business as usual” in order to make acceptable what is not, the second one participates of a deep political renewal claim in order to ensure the effectiveness of the sustainable transition of urban systems.